A global survey on occupational health services in selected international commission on occupational health (ICOH) member countries - Jorma Rantanen; Suvi Lehtinen; Antonio Valenti; Sergio Iavicoli (BMC, 2017)
Abstract Background The United Nations General Assembly (UNGA), the International Labour Organization (ILO), the World Health Organization (WHO), the International Commission on Occupational Health (ICOH), and the European Union (EU) have encouraged countries to organize occupational health services (OHS) for all working people irrespective of the sector of economy, size of enterprise or mode of employment of the worker. The objective of this study was to survey the status of OHS in a sample of countries from all continents. Methods A questionnaire focusing on the main aspects of OHS was developed on the basis of ILO Convention No. 161 and several other questionnaire surveys used in various target groups of OHS. The questionnaire was sent to 58 key informants: ICOH National Secretaries. Results A total of 49 National Secretaries responded (response rate 84.5%), from countries that employ 70% of the total world labour force. The majority of the respondent countries, 67%, had drawn up an OHS policy and implement it with the help of national occupational safety and health (OSH) authorities, institutes of occupational health or respective bodies, universities, and professional associations. Multidisciplinary expert OHS resources were available in the majority (82%) of countries, but varied widely in quantitative terms. The average OHS coverage of workers was 24.8%, with wide variation between countries. In over two thirds (69%) of the countries, the content of services was mixed, consisting of preventive and curative services, and in 29% preventive only. OHS financing was organized according to a mixed model among 63% and by employers only among 33% of the respondents. Conclusions The majority of countries have drawn up policies, strategies and programmes for OHS. The infrastructures and institutional and human resources for the implementation of strategies, however, remain insufficient in the majority of countries (implementation gap). Qualitatively, the content and multidisciplinary nature of OHS corresponds to international guidance, but the coverage, comprehensiveness and content of services remain largely incomplete due to a lack of infrastructure and shortage of multiprofessional human resources (capacity gap). The estimated coverage of services in the study group was low; only a quarter of the total employed population (coverage gap).